뽕나무 재배기간 중 기상환경과 눈마름병 발생관계 분석 - 김주희(Ju-hee Kim); 최인영(In-young Choi); 김주(Ju Kim); 이장호(Jang-ho Lee) (Sigmulbyeong yeon'gu, 2017)
The twig blight of mulberry caused by Fusarium lateritium occurs mainly in Buan area, which is the main area of mulberry. The initial symptom on twigs showed dark edge blight and dark orange tiny particles on the spot, and it was withered and died. In the case of mulberry twig blight, the difference in the degree of occurrence between the years is intense, and an average of 2.7% occurred in Buan in 2013, but in 2014, it was difficult to search for the generated fields. In order to find the cause of the difference in the incidence of mulberry twig blight, we investigated and analyzed the weather conditions during cultivation and as a result, the occurrence of the disease increased under the condition that the temperature of the spring was lower and the number of days passing below the winter freezing point increased. In addition, it was analyzed that the occurrence of the next year increases when the rainfall is high and the number of sunshine is low after removing the harvested branches. Therefore, in the event that weather conditions causing twig blight diseases have elapsed, it is necessary to prevent the disease by spraying the registered applied fungicide prophylactically. Fusarium lateritium에 의해 발생하는 뽕나무 눈마름병이 전북지역 뽕나무 주산지인 부안지역을 중심으로 발생하였다. 눈마름병이 걸린 가지는 병반 중심부가 약간 오목한 상태의 둥근타원형의 병반을 형성하며 병반 위에 주황색 작은 입자들이 밀생하였다. 뽕나무 가지 위에 병반이 형성된 위쪽으로는 눈이 검게 변하고 말라서 눈이 틔지 않고 말라 죽거나 생육을 약화시키고 심한 경우 결과지가 검게 변하고 말라서 수량 감소를 초래하기도 한다. 뽕나무 눈마름병은 연차 간 발생정도 차이가 심하여 2013년도 전라북도에서 평균적으로 3.2% 발생을 하였으나 2014년도에는 발생한 포장을 찾기가 어려울 정도로 발생이 없었다. 발생차이의 원인을 찾기 위해 재배 중 기상조건을 조사분석한 결과 봄철의 온도가 낮거나 겨울철 영하이하로 경과하는 일수가 증가하는 조건에서 병 발생이 증가하고, 수확하고 난 결과지를 제거한 후에 강우량이 많고 일조시수가 낮은 조건이 경과할 경우 이듬해 발생이 증가하는 것으로 분석되었다. 그러므로 눈마름병이 다발생 할 수 있는 조건이 경과되었을 때는 적용 약제를 예방적으로 살포하여 피해를 최소화하여야 할 것이다.